Penggunaan Serbuk Piper ornatum sebagai biopesticide larva lalat rumah Musca domestica - Anita Dewi Moelyaningrum; Violita Pita Nugraheni; Prehatin Trirahayu Ningrum (BIOEDUSCIENCE, 2020)
Background: Red betel (Piper ornatum) contains several compounds including flavonoids, alkaloids, tannins, and essential oils that have the ability as bioinsecticides. The purpose of this study was to analyze the differences in the number of deaths of house fly larvae (Musca domestica) exposed to red betel in the control group (0%) and the treatment group with a concentration of 1%; 1.5% and 2% for 24 hours. Methods: used is true experimental method with only posttes control group design. There were 4 treatments with 6 replications per treatment. Each treatment was described on 8 larvae, so the number of larvae used in this study was 192 tails. Results: Research shows that red betel powder is indeed effective in killing Musca domestica larvae, but it still requires a long time, which is at least 24 hours. Concentration is needed at least 2% if used as a biopesticide to reduce the density of flies. Conclusion: There was no significant difference in the mortality of Musca domestica larvae in the administration of red betel powder (Piper ornatum.